2022
DOI: 10.1039/d2cc02643k
|View full text |Cite
|
Sign up to set email alerts
|

Genetic encoding of ε-N-l-lactyllysine for detecting delactylase activity in living cells

Abstract: Lysine ε-N-L-lactylation is a newly discovered post-translational modification. Herein we present the genetic encoding of ε-N-L-lactyllysine in bacterial and mammalian cells, allowing preparation of site-specifically ε-N-L-lactylated recombinant proteins and construction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In addition to the enzymatic transfer of lactyl-CoA to lysine, lactyl-glutathione (LGSH) is hydrolyzed by glyoxalase 2 (GLO2) to generate glutathione and D-lactate, the lactate moiety is nonenzymatically transferred from LGSH to lysine residues to form lactylation modifications (95). Recent studies have shown that Class I histone deacetylases (HDAC1-3) act as erasers to exhibit delactylase activity in vitro (96, 97), Sirtuins are potential nonhistone delactate enzymes (98). However, it is not clear which enzymes produce the intermediate molecule Lactyl-CoA, which enzymes recognize histone lactylation as "readers", and more "writers" and "eraser" are yet to be discovered (Figure 3B).…”
Section: Lactylation Of Hcc Histone Lactylationmentioning
confidence: 99%
“…In addition to the enzymatic transfer of lactyl-CoA to lysine, lactyl-glutathione (LGSH) is hydrolyzed by glyoxalase 2 (GLO2) to generate glutathione and D-lactate, the lactate moiety is nonenzymatically transferred from LGSH to lysine residues to form lactylation modifications (95). Recent studies have shown that Class I histone deacetylases (HDAC1-3) act as erasers to exhibit delactylase activity in vitro (96, 97), Sirtuins are potential nonhistone delactate enzymes (98). However, it is not clear which enzymes produce the intermediate molecule Lactyl-CoA, which enzymes recognize histone lactylation as "readers", and more "writers" and "eraser" are yet to be discovered (Figure 3B).…”
Section: Lactylation Of Hcc Histone Lactylationmentioning
confidence: 99%
“…For example, to explore the regulation of lysine lactylation, we incorporated LacK (Figure 2b) into EGFP and firefly luciferase at the essential lysine residues and constructed fluorescent and luminescent probes, respectively, for detecting cellular delactylases that can remove lysine lactylation. Using these genetically encoded probes, we demonstrated that sirtuin 1 is the potential delactylase for non-histone proteins, suggesting new regulatory mechanisms for this novel modification (Sun, Chen, Xu, et al, 2022).…”
Section: Lysine Acylationmentioning
confidence: 99%
“…Taking advantage of the substrate promiscuousness of the Pyl pairs, various acylation‐bearing UAAs (Figure 2b), that is, ε‐ N ‐acyl‐lysines, such as ε‐ N ‐formyl‐lysine (ForK; Wang et al, 2015), ε‐ N ‐propionyl‐lysine (PrK; Gattner et al, 2013; Wilkins et al, 2015), ε‐ N ‐butyryl‐lysine (BuK; Gattner et al, 2013; Wilkins et al, 2015), ε‐ N ‐crotonyl‐lysine (CrK; Gattner et al, 2013; Kim et al, 2012; Wilkins et al, 2015), ε‐ N ‐2‐hydroxyisobutyryl‐lysine (HibK; Xiao et al, 2015), ε‐ N ‐benzoyl‐lysine (BzK; Cao et al, 2021; Ji et al, 2021; Tian et al, 2021), ε‐ N ‐ L ‐lactyl‐lysine (LacK; Ren et al, 2022; Sun, Chen, Xu, et al, 2022), ε‐ N ‐β‐hydroxybutyryl‐lysine (BhbK; Ren et al, 2022), ε‐ N ‐lipoyl‐lysine (LipoK; Ren et al, 2022), ε‐ N ‐heptanoyl‐lysine (HepoK; Fu et al, 2019), and ε‐ N ‐( L ‐threonyl)‐lysine (ThrK; Zang et al, 2022), have been developed and site‐specifically incorporated into proteins in bacterial cells, enabling the production of recombinant acylation‐bearing proteins such as core histone proteins H2B, H3, and H4. As a recent example for functional studies, Wan et al prepared recombinant fructose‐bisphosphate aldolase A (ALDOA) with site‐specific lactylation, a newly identified type of lysine acylation in histone and non‐histone proteins (Sun, Chen, & Peng, 2022; Zhang et al, 2019), and showed that K147 lactylation inhibits the activity of this glycolytic enzyme (Wan et al, 2022).…”
Section: Lysine Modificationsmentioning
confidence: 99%
“…One major discovery in the sirtuin field has been that many sirtuins each possesses multiple deacylase activities acting on N ε ‐acyl‐lysine substrates with different acyl groups (Figure 1) (Abmayr & Workman, 2019; Anderson et al., 2017; Bheda et al., 2016; Chen et al., 2015; Chio et al., 2023; Colak et al., 2013; Delaney et al., 2021; Dong et al., 2022; Fan et al., 2023; Feldman et al., 2013; Gil et al., 2013; Huang, Zhang, et al., 2018; Ji et al., 2021; Jin et al., 2016, 2023; Li & Zheng, 2018; Liu et al., 2020; Mikulik et al., 2012; Olesen et al., 2018; Rajabi et al., 2018; Ringel et al., 2014; Seidel et al., 2016; Sun et al., 2022; Tan et al., 2022; Teng et al., 2015; Wang et al., 2023; Zhang et al., 2023; Zhang, Cao, et al., 2019; Zhang, Li, et al., 2019; Zhu et al., 2012; Zu et al., 2022). Specifically, SIRT1/2/3 are all able to catalyze efficiently the deacetylation and defatty‐acylation (e.g., demyristoylation) reactions; CobB from certain bacterial strains is able to catalyze the deacetylation and desuccinylation reactions with comparable catalytic efficiency; CobB from Escherichia coli was further found to catalyze the delactylation reaction with comparable catalytic efficiency to its deacetylase activity; SIRT1 is also able to catalyze deformylation reaction albeit being ~6.6‐fold less proficient than its deacetylase activity; SIRT1 was further found to be an in vivo debenzoylase and delactylase; SIRT2 is also able to catalyze debenzoylation, demethacrylation, and de‐4‐oxononanoylation (de‐4‐ONylation) reactions with more or less comparable catalytic proficiency to that of deacetylation; SIRT2 and SIRT3 were also found to possess an in vivo delactylase activity; SIRT3 is also capable of catalyzing proficiently the decrotonylation and de‐β‐hydroxybutyrylation reactions; SIRT4 is able to catalyze proficiently the deglutarylation and de‐3‐methyl‐glutarylation reactions; SIRT5 is able to catalyze proficiently the demalonylation, desuccinylation, and deglutarylation reactions; SIRT6 was found to catalyze both deacetylation and defattyl‐acylation (e.g., demyristoylation) reactions, with the former activity being weaker than the latter activity on isolated protein substrates; however, the former activity can be enhanced when the substrates are core histone proteins present in a nucleosome unit together with double‐stranded DNA (dsDNA), which has been rationalized very recen...…”
Section: Introductionmentioning
confidence: 99%